Multi-Institutional Analysis of Synchronous Prostate and Rectosigmoid Cancers - Jacobs, Corbin D.; Trotter, Jacob; Palta, Manisha; Moravan, Michael J.; Wu, Yuan; Willett, Christopher G.; Lee, W. Robert; Czito, Brian G. (Frontiers in Oncology, 2020)
Purpose: To perform a multi-institutional analysis of patients with synchronous prostate and rectosigmoid cancers. Materials and Methods: A retrospective review of Duke University and Durham Veterans Affairs Medical Center records was performed for men with both prostate and rectosigmoid adenocarcinomas from 1988-2017. Synchronous presentation was defined as symptoms, diagnosis, or treatment of both cancers within 12 months of each other. The primary study endpoint was overall survival. Univariate and multivariable Cox regression was performed. Results: Among 31,883 men with prostate cancer, 330 (1%) also had rectosigmoid cancer and 54 (16%) of these were synchronous. Prostate cancer was more commonly the initial diagnosis (59%). Fifteen (28%) underwent prostatectomy or radiotherapy before an established diagnosis of rectosigmoid cancer. Stage I, II-III or IV rectosigmoid cancer was present in 26%, 57%, and 17% of men, respectively. At a median follow-up of 43 months, there were 18 deaths due rectosigmoid cancer and two deaths due to prostate cancer. Crude late grade ≥3 toxicities include nine (17%) gastrointestinal and six (11%) genitourinary. Two anastomotic leaks following low anterior resection occurred in men who received a neoadjuvant radiotherapy prostate dose of 70.6-76.4 Gy. Rectosigmoid cancer stages II-III (HR 4.3, p=0.02) and IV (HR 16, p<0.01) as well as stage IV prostate cancer (HR 31, p<0.01) were associated with overall survival on multivariable analysis. Conclusions: Synchronous rectosigmoid cancer is a greater contributor to mortality than prostate cancer. Men aged ≥45 with localized prostate cancer should undergo colorectal cancer screening prior to treatment to evaluate for synchronous rectosigmoid cancer.